Comparative studies on microstructures, strengths and reliabilities of two types of AlN direct bonding copper substrates. Issue 15 (15th October 2018) - Wei, Xin; Xu, Haixian; Zhan, Jun; Zhang, Hao; Cao, Ye; Cui, Song; Tang, Wenming
Abstract: Oxidation of AlN ceramic plates was performed via two different techniques of Cu 2+ activation followed by oxidation and direct oxidation. Two types of AlN direct bonding copper (DBC) substrates were then fabricated by combining the pre-oxidized Cu foils with the AlN plates. The interface structures, the peel strengths, and the temperature cycling reliabilities of the samples are investigated. The results showed that after Cu 2+ activation followed by oxidation, rod-like CuAl2 O4 particles were distributed on the dense α-Al2 O3 layer oxide layer of the AlN plates. This microstructure is beneficial in improving the interface bonding strength and the wettability of the AlN-DBC substrates. Interface layers of both the AlN-DBC substrates were composed of two sublayers of Cu2 O+CuAlO2 and residual Al2 O3 . During the peeling process, fractures occurred in the AlN plates for the Cu 2+ activated and oxidized AlN-DBC substrates, but at the interface layer for the directly oxidized AlN-DBC substrates. The peel strength and the temperature cycling performance of the Cu 2+ activated and oxidized AlN-DBC substrates were higher than the directly oxidized AlN-DBC substrates.